Knowledge and Attitude on Eye Donation among Undergraduate Medical Students of Kathmandu University School of Medical Sciences, Nepal - Kaiti, R.; Dhungel, P.; Pradhan, A.; Chaudhry, M. (Kathmandu University Medical Journal, 2021)
Background Corneal blindness accounts for a significant proportion of avoidable visual impairment in developing countries. Eye donation is voluntary and awareness in undergraduate medical students being a future practitioner in any field are expected to be linked to patients during death in hospitals. Objective To assess the awareness of medical students on eye donation at Kathmandu University School of Medical Sciences (KUSMS). Method This was a cross-sectional study conducted among undergraduate medical students of KUSMS. Students’ responses were recorded using a predesigned, pretested, semi-structured questionnaire inquiring knowledge and attitude of eye donation, sources of information, their willingness to donate eyes as well as the reasons for donating/ not donating eyes. Result Less than half of the medical students (45.6%) were aware of eye donation only after death. Newspapers (72.2%) were the major source of information. The final year medical students were more aware (Average knowledge score = 11.56 ± 2.05) than their juniors. 80.7% of the students were willing to donate their eyes. The adjudged reasons for willingness to donate were that eye donation is a noble work and pleasure in helping a blind person while the reasons for unwillingness to donate were lack of awareness followed by family objection to eye donation. Conclusion Future medical practitioners possessed satisfactory knowledge about eye donation. Educating this cadre of human resources to sensitize them towards the need for eye donation would be a crucial step towards reducing the global burden of corneal blindness.